Associated adverse health outcomes of polypharmacy and potentially inappropriate medications in community-dwelling older adults with diabetes - Lu, Lvliang; Wang, Shuang; Chen, Jiaqi; Yang, Yujie; Wang, Kai; Zheng, Jing; Guo, Pi; Cai, Yunpeng; Zhang, Qingying (Frontiers in Pharmacology, 2023)
Purpose: This study aimed to identify the association of chronic polypharmacy and potentially inappropriate medications (PIMs) with adverse health outcomes (AHO) in communitydwelling older adults with diabetes in China.A 2-year retrospective cohort study was conducted using 11829 communityfollowed older adults with diabetes and medical records from 83 hospitals and 702 primary care centers in Shenzhen, China. Chronic polypharmacy and PIMs were identified from † Lvliang Lu 1 † and Shuang Wang 2 † share first authorship ‡ Qingying Zhang 1 ‡ and Yunpeng Cai 3 ‡ share corresponding authorship Associated AHO of polypharmacy and PIMs prescription records using Beers' criteria, and their associated AHO was analyzed using multivariable logistic regression analysis.The prevalence of chronic polypharmacy and at least one PIM exposure was 46.37% and 55.09%, respectively. The top five PIMs were diuretics, benzodiazepines, first-generation antihistamines, sulfonylureas, and insulin (sliding scale). Chronic polypharmacy was positively associated with all-cause hospital admission, admission for coronary heart disease, admission for stroke, admission for dementia, and emergency department visits. Exposure to PIMs was positively associated with all-cause hospital admission, admission for heart failure (PIMs ≥ 2), admission for stroke (PIMs ≥ 3), emergency department visits, bone fracture, constipation, and diarrhea.Conclusions: Chronic polypharmacy and PIMs were prevalent in older adults with diabetes in Chinese communities. Iatrogenic exposure to chronic polypharmacy and PIMs is associated with a higher incidence of different AHO. This observational evidence highlights the necessity of patient-centered medication reviews for chronic polypharmacy and PIMs use in older patients with diabetes in primary care facilities in China and attract attention for the caution of polypharmacy especially PIM using in older adults with diabetes in clinical practice.